2012
DOI: 10.1037/a0028989
|View full text |Cite
|
Sign up to set email alerts
|

Brain representations of negative numbers.

Abstract: Participants performed a physical comparison task of pairs of positive and pairs of negative one-digit numbers while their electrophysiological brain activity was measured. The numerical value of the presented digits was either congruent or incongruent with the physical size of the digits. Analysis has shown that the earliest event-related potential (ERP) difference between positive and negative numbers was found in the P300 ERP component peak, where there was an inverse effect of congruity in the negative pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…The selection of ERP components and latencies for analysis was guided by previous research (e.g., Dehaene, 1996 ; Temple and Posner, 1998 ; Schwarz and Heinze, 1998 ; Cohen Kadosh et al, 2007 ; Libertus et al, 2007 ; Szűcs and Soltész, 2007 ; Szűcs et al, 2007 , 2009 ; Hyde and Spelke, 2009 , 2012 ; Parnes et al, 2012 ) and confirmed by visual inspection of the grand-average waveforms and topographical maps across participants. We identified three time windows corresponding to the three observed ERP components of interest: N1 (covering the first posterior negative-going deflection that follows the P1; 165–200 ms), P2p (covering the second posterior positive-going deflection; 230–280 ms), and P3 (covering an extended positive-going deflection over both centro-parietal and posterior sites; 300–370 ms).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The selection of ERP components and latencies for analysis was guided by previous research (e.g., Dehaene, 1996 ; Temple and Posner, 1998 ; Schwarz and Heinze, 1998 ; Cohen Kadosh et al, 2007 ; Libertus et al, 2007 ; Szűcs and Soltész, 2007 ; Szűcs et al, 2007 , 2009 ; Hyde and Spelke, 2009 , 2012 ; Parnes et al, 2012 ) and confirmed by visual inspection of the grand-average waveforms and topographical maps across participants. We identified three time windows corresponding to the three observed ERP components of interest: N1 (covering the first posterior negative-going deflection that follows the P1; 165–200 ms), P2p (covering the second posterior positive-going deflection; 230–280 ms), and P3 (covering an extended positive-going deflection over both centro-parietal and posterior sites; 300–370 ms).…”
Section: Methodsmentioning
confidence: 99%
“…The reaction time (RT) difference between these two conditions (i.e., incongruent minus congruent) is referred to as the size congruity effect (SiCE). The SiCE has been frequently used as a marker for the automatic processing of numbers and was found to be enlarged for pairs with larger compared to smaller intrapair distance (e.g., Henik and Tzelgov, 1982 ; Tzelgov et al, 1992 ; Pansky and Algom, 1999 ; Schwarz and Ischebeck, 2003 ; Cohen Kadosh et al, 2007 ; Parnes et al, 2012 ; Pinhas and Tzelgov, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, a person would compare -5 with -6 on the basis of the relative positions of these numbers on the mental number line: -5 is to the right of -6, so -5 > -6. Various researchers have tested these and related hypotheses for the mental processing involved in comparing integers (e.g., Fischer, 2003;Ganor-Stern & Tzelgov, 2008;Krajcsi & Igács, 2010;Parnes, Berger, & Tzelgov, 2012;Varma & Schwartz, 2011).…”
Section: Psychological Experiments Concerning Integer Comparisonsmentioning
confidence: 99%
“…When comparing natural numbers, people responded faster on the left side when comparing small numbers, and they responded faster on the right side when comparing larger numbers (e.g., Fischer, 2003). The SNARC effect is generally regarded as evidence of the use of a "mental number line," which may or may not include negative numbers (e.g., Gullick & Wolford, 2012;Huber, Cornelsen, Korbinian, & Nuerk, 2015;Parnes et al, 2012).…”
Section: Psychological Experiments Concerning Integer Comparisonsmentioning
confidence: 99%